2010
DOI: 10.1007/s12280-010-9155-9
|View full text |Cite
|
Sign up to set email alerts
|

Wind Farms and Community Engagement in Australia: A Critical Analysis for Policy Learning

Abstract: In late 2007, after signing the Kyoto Protocol, a new Australian federal government committed to generating 20% of Australia's electricity from renewable energy by 2020, for a transition to a low-carbon economy. With wind energy the most viable technology for such expansion, little recognition, however, was paid to intense social conflict surrounding wind farm location. By 2006, inadequate community engagement had emerged as the primary governance issue underpinning a host of issues that local communities face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 63 publications
(60 reference statements)
1
19
1
Order By: Relevance
“…This has led to a sense of trepidation amongst developers about public opposition and an unfortunate feeling of unease about the viability and integrity of the sector. Research has shown that communities are often divided over the perceived and actual benefits of these developments, with some landholders benefitting financially from a proposed development, while others in the surrounding region feel disadvantaged (Hall et al 2013;Hindmarsh 2010). This dynamic has resulted in an active and politically prominent opposition movement developing.…”
Section: Wind Farm Development and The Community Engagement Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to a sense of trepidation amongst developers about public opposition and an unfortunate feeling of unease about the viability and integrity of the sector. Research has shown that communities are often divided over the perceived and actual benefits of these developments, with some landholders benefitting financially from a proposed development, while others in the surrounding region feel disadvantaged (Hall et al 2013;Hindmarsh 2010). This dynamic has resulted in an active and politically prominent opposition movement developing.…”
Section: Wind Farm Development and The Community Engagement Frameworkmentioning
confidence: 99%
“…This dynamic has resulted in an active and politically prominent opposition movement developing. The high visibility of wind farm turbines across the landscape provides a focus for dissatisfaction, and opposition movements rely on controversial and contested claims of wind farm impacts from turbine noise, glint and vibration (Hindmarsh 2010;Chapman 2013).…”
Section: Wind Farm Development and The Community Engagement Frameworkmentioning
confidence: 99%
“…Stakeholder "engagement is critical to achieve a social licence to operate, but its capacity to influence social licence is not well understood" (Dare, Schirmer, & Vanclay, 2014, p. 188). Failure to engage communities in a meaningful way in the SLO process is seen to be the predominant cause of social conflict in resource management (Hall & Jeanneret, 2015;Hindmarsh, 2010;Lloyd, Luke, & Boyd, 2014;Pullin & Knight, 2003). The process of meaningful stakeholder engagement is also central to overcoming such conflict, but it is a high-risk, high-cost issue in resource management.…”
Section: Engagement As a Foundation For Slomentioning
confidence: 99%
“…Stakeholder perceptions may be influenced by the engagement stakeholders have with a given company. Consequences can be dire and costly when stakeholder engagement is not constructive Hindmarsh, 2010). suggest that dissenting communities often unite around perceived negative impacts of resource development, with dissent often arising from lack of communication.…”
Section: Dialogue As 'Meaningful' Stakeholder Engagementmentioning
confidence: 99%
See 1 more Smart Citation